EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA PADA MATERI SEGIEMPAT - Vemsi Damopolii; Nursiya Bito; Resmawan Resmawan (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2019)
The descriptive study aims to elaborate on the effectiveness of multimedia-based mathematics learning process in a lesson on the rectangular shape in 7th-grade students in SMP Negeri 11 Gorontalo. There are four indicators investigated in this study, i.e., 1) Teacher’s competence in learning management, 2) Students’ activity during the learning process, 3) Students’ learning outcome, and 4) Students’ response. The result shows that the implementation of rectangular multimedia in the mathematics learning process is categorized effectively. The teachers’ competence in learning management results in effective criteria, included in quite good category. Moreover, the students’ activity is categorized in effective criteria, as the overall percentage meets the minimum effectiveness criteria set. Further, the students’ learning outcome passes the classical competence, as 85 percent achieve score of 70 or more. The students’ response on the learning process also meets the effectiveness criteria; 84 percent of students respond positively or very positively towards the learning multimedia.